Predicting of Impact Strength and Elastic Modulus of Polypropylene/EPDM/Graphene/Glass Fiber Nanocomposites by Response Surface Methodology - Ashenai Ghasemi, Faramarz (Array, 2021)
In the present manuscript, Response Surface Method (RSM) of the experimental planning was applied to optimize the mechanical properties such as impact strength and elastic modulus of polypropylene (PP)/ethylene propylene dine monomer (EPDM) /grapheme Nano sheets (GnPs)/ glass fiber hybrid nanocomposites. According to a Box-Behnken method, three levels of parameters were used for EPDM (5, 10 and 15 wt.%), GnPs (0, 1 and 2 wt.%) and glass fiber (10, 20 and 30 wt.%). In addition, specimens were studied using differential scanning calorimeter (DSC) and scanning electron microscopy (SEM) to see their morphology and thermal properties. It was discovered that GnPs, glass fiber and EPDM played an important role in impact strength and elastic modulus of the nanocomposites. To reach the maximum value of the impact strength and elastic modulus simultaneously, the best amount of additives was about 0.82 wt.% of GnPs, 30 wt.% of glass fiber and 15 wt.% of EPDM. The gained R2 values and the corresponding diagrams showed a desirable accordance (above 0.93 for all the responses) with the experiments and those guessed by the RSM.